2014
DOI: 10.2147/dddt.s67370
|View full text |Cite
|
Sign up to set email alerts
|

Studies of synthetic chalcone derivatives as potential inhibitors of secretory phospholipase A2, cyclooxygenases, lipoxygenase and pro-inflammatory cytokines

Abstract: Arachidonic acid metabolism leads to the generation of key lipid mediators which play a fundamental role during inflammation. The inhibition of enzymes involved in arachidonic acid metabolism has been considered as a synergistic anti-inflammatory effect with enhanced spectrum of activity. A series of 1,3-diphenyl-2-propen-1-one derivatives were investigated for anti-inflammatory related activities involving inhibition of secretory phospholipase A2, cyclooxygenases, soybean lipoxygenase, and lipopolysaccharides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 36 publications
(42 reference statements)
0
36
0
1
Order By: Relevance
“…Earlier reports suggest binding of chalcones to molecular targets such as HIF1α , phospholipase A2 and tubulin polymerization in cancer cells. In our molecular docking study, we observed that the R‐configuration (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Earlier reports suggest binding of chalcones to molecular targets such as HIF1α , phospholipase A2 and tubulin polymerization in cancer cells. In our molecular docking study, we observed that the R‐configuration (Fig.…”
Section: Resultsmentioning
confidence: 98%
“… 72 3-(2,3-dimethoxy-phenyl)-1-naphthalene-1-yl-propenone ( 34 ) and 4-(4-diethylamino-phenyl)-1,1-diphenyl-but-3-en-2-one ( 35 ) were also reported to suppress the secretion of IL-6 and TNF-α in LPS-induced RAW 264.7 macrophages. 73 Two β-chlorovinyl chalcones, with chemical structures of 5-(4-bromo-phenyl)-5- chloro-1-(4-methoxy-phenyl)-penta-2,4-dien-1-one ( 36 ) and 5-chloro-5-(4-chloro-phenyl)-1-(4-methoxy-phenyl)-1-penta-2,4-dien-1-one ( 37 ), also exhibited significant suppression of LPS-induced IL-6 and TNF-α production in THP-1 cells. 74 Okanin ( 38 ), a natural chalcone isolated from the genus Bidens and 3-penten-2-one were found to be able to suppress LPS-induced NO production and iNOS expression in RAW264.7 macrophages through upregulation of HO-1 expression.…”
Section: Chalcones As Immunomodulatory Agentsmentioning
confidence: 99%
“…13,14 It is also noted from literature that the inhibition of more than one enzyme involved in different pathways of arachidonic acid metabolism lead to a synergistic anti-inflammatory effect with enhanced spectrum of activity. [15][16][17] The virtual combinatorial library is generated routinely for small molecules during the drug discovery cycle and screened based on their predicted physicochemical properties, activities, specificities, etc. [18][19][20] The virtual screening is useful in selecting a smaller set of promising hits from a large set of compound libraries.…”
Section: Introductionmentioning
confidence: 99%